Dual‐Modal Dielectric Elastomer System for Simultaneous Energy Harvesting and Actuation - Zhiyuan Zhang; Wenwei Huang; Shaodi Zheng; Jianbo Tan; Jinzhan Cheng; Jiancheng Cai; Shiju E; Zisheng Xu (Advanced Science)
Abstract Dielectric elastomers (DEs) have promising capabilities for soft electromechanical systems, including those for actuation and energy generation. However, their widespread application is restricted by electromechanical instability (EMI) and the requirement for high‐voltage operation. This study presents a dual‐modal DE system that effectively overcomes these limitations by leveraging a dual‐membrane structure. The proposed structure not only suppresses EMI through charge sharing but also enables simultaneous energy harvesting and actuation, enhancing the overall electrical performance of the system. The system demonstrated a remarkable improvement in output performance, exceeding that of traditional single‐modal DE generators by up to 30%. The practicality of the system is developed by integrating it into a mechanically powered soft robot capable of locomotion and environmental monitoring using a wireless temperature sensor. This study paves the way for the development of advanced DE‐based systems with enhanced stability, functionality, and potential for diverse applications in soft robotics, energy harvesting, and other areas that require coupled electromechanical capabilities.